2009
DOI: 10.1002/mus.21330
|View full text |Cite
|
Sign up to set email alerts
|

Changes in joint angle, muscle‐tendon complex length, muscle contractile tissue displacement, and modulation of EMG activity during acute whole‐body vibration

Abstract: It has been suggested that vibration causes small changes in muscle length, but to the best of our knowledge, these have yet to be demonstrated during whole-body vibration (WBV). This was an observational study to determine whether acute WBV would result in muscle lengthening. We hypothesized that acute WBV would increase electromyography (EMG) activity concurrently with measurable changes in muscle contractile length. Nine healthy males performed two conditions on a Galileo vibration machine for 15 s at 0 HZ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(69 citation statements)
references
References 28 publications
0
66
0
3
Order By: Relevance
“…WBV is thought to elicit muscle contractions through spinal reXexes (Cardinale and Bosco 2003;Cochrane et al 2009;Rittweger et al 2003). However, and in contrast to other exercise modalities, stretch and H-reXexes are typically suppressed during isolated muscle vibration (Arcangel et al 1971;de Gail et al 1966).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…WBV is thought to elicit muscle contractions through spinal reXexes (Cardinale and Bosco 2003;Cochrane et al 2009;Rittweger et al 2003). However, and in contrast to other exercise modalities, stretch and H-reXexes are typically suppressed during isolated muscle vibration (Arcangel et al 1971;de Gail et al 1966).…”
Section: Discussionmentioning
confidence: 99%
“…The results that WBV does not enhance spinal reXex excitability are supported by the Wnding that superimposing the Jendrassik manoeuvre upon WBV failed to enhance metabolic rate (Cochrane et al 2008a). Nevertheless, stretch reXexes seem to be active during WBV, as we have reported a temporal association between EMG activity and muscle contractility; however, WBV was only performed at a very low frequency (6 Hz) (Cochrane et al 2009). It is possible that the acute eVects of WBV are related to its inXuence on nonneurally mediated events during the contractile process, such as those which occur distal to the neuromuscular junction.…”
Section: Introductionmentioning
confidence: 92%
“…It is obvious, however, that the human body is not completely rigid, but rather has elastic and damping properties. Nevertheless, the feet can sometimes be lifted off the platform during whole body vibration exercise, which leads to a loss of contact and skidding elongated by 1% of its total length during 6 Hz vibration cycles with a Peak = 0.6g (Cochrane et al 2009). …”
Section: Muscle and Tendon Mechanicsmentioning
confidence: 98%
“…It has been demonstrated that vibration exercise can elicit a stretch reflex response similar to the tonic vibration reflex (Pollock et al 2012;Ritzmann et al 2010), which can result in increased motor unit recruitment and/or firing rate (Pollock et al 2012; Ritzmann et al 2010). In the same way, it has also been suggested that during vibration exercise the muscle tendon units are stretched in every vibration cycle (Cochrane et al 2009), which could induce a frequencydependent activation of the muscles spindles that elicit the stretch reflex responses detectable in the EMG signal (Ritzmann et al 2010). If it is the case, it can be speculated that the observed vibration-induced increase in TB agonist activation at the highest f out was caused, at least in part, by a greater number of stretch reflex responses compared to lower f out .…”
Section: Discussionmentioning
confidence: 97%